Sense of Coherence and Physical Health. The Emotional Sense of Coherence (SOC-E) was Found to be the Best-Known Predictor of Physical Health - Trine Flensborg-Madsen; Søren Ventegodt; Joav Merrick (The Scientific World Journal)
In this study, we created a measure for emotionality named the emotional sense of coherence (SOC-E). We found that SOC-E was significantly associated with physical health (r = 0.266; p < 0.05), while it was not significantly associated with psychological health (r = 0.006; NS). Based on a correlation matrix, we constructed a new scale, the SOC-E II, which was even better associated with physical health (r = 0.362) and also associated with psychological health (r = 0.259; p < 0.01). Our results showed that SOC-E and SOC-E II were better predictors of physical health than the SOC scales developed by Aaron Antonovsky (1923–1994) (SOC-29 and SOC-13). We conclude that emotional coherence is important for physical health, but it is not important in the same way for psychological health. In a previous study, we found that a mental operationalization of Antonovsky's sense of coherence was highly associated with psychological health and not associated with physical health. Based on these two studies, we conclude that physical health is primarily associated with emotions, while psychological health is primarily associated with mentality.